PERANCANGAN SISTEM INFORMASI REKAM MEDIS PASIEN RAWAT JALAN BERBASIS WEB DENGAN FRAMEWORK YII DI KLINIK SEHAT MARGASARI BANDUNG - Pasaribu, Johni S (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2017)
Medical record patient information system is a system that aims to manage the data of patients who register for treatment until the patient is discharged from the hospital or health center in a given period. The information system is important because it is designed to prevent errors in the execution of the procedure of registration and data management so that it can be done as well as possible. This information systems in health clinic is an information system that has patient data, drug data, transaction data and medical records of the patient. As for the performance of the system in patient care in health clinic in generally not optimal because it is still in the processing of patient data and medical records are still using books or manuals. Therefore care patients at health clinic become ineffective and inefficient, because bookkeeping making slow reporting. Patient care information system designed aiming to establish a computerized information system , making it easier for the health clinic process patient data, drugs, transaction and patient medical records to be reported. The expected outcome of this research is to produce medical record patient information system web-based using YII Framework with MVC method at Health Clinic Margasari which can solve problem. Fundamental problem of this research is how to install information system for medical record patient information system at Health Clinic Margasari that make information representation accurately and efficiently. The aim of this research is to produce a program of application system